Amphibians of Lake Sebu, South Cotabato assessment of the species composition and existing potential threats on the seven falls of Barangay Lake Lahit - Rovillos, Kliendio P. (2008)
Field work was done to identify existing threats and provide benchmark information on the amphibian species composition of the Seven Falls of Barangay Lake Lahit, in the months of May and October 2007. Using the visual encounter technique, results revealed 17 amphibians species, 16 anurans and one caecilian from five representative families which included one from the family Pelobatidae; two from theBufonidae family; 10 from the family Ranidae; three from the family Rhacophoridae, and one from the Caeciliidae family. Eight species were endemic (47.06% endemism) to the Philippines with two of them being found only in Mindanao (11.76%). Two species were identified as nearly threatened, another two were vulnerable, and one was rare in status in the country. The developmental and economic activities, habitat destruction, habitat fragmentation, irresponsible tourism and waste disposal, and the agricultural run-offs existing within and outside the Seven Falls area as well as the high risks of water contamination from excessive use of tilapia fish feeds on Lake Sebu and Lake Seloton were identified to pose possible detrimental effects on amphibian populations. Of more concern were the activities outside of the barangay, particularly on tilapia farming practices in the two economically important lakes and the agricultural run-offs from farms surrounding the stream sources of the Seven Falls. These are contributing factors that could result to water pollution. This requires attention and further study as results showed high reliance of documented anuran species on stream water